Financial accounting - Stice, Earl K.; Stice, James D.; Albrecht, W. Steve; Swain, Monte R. (Singapore Cengage learning, 2014)
Contents: financial reporting and the accounting cycle; operating activities; investing and financing activities.
Includes index
Keywords: Kế toán